Ultimate bending performance and fatigue life of U-shaped metal bellows. (August 2022) - Hao, Zengliang; Chen, Yuhang; Chen, Lihuan; Cai, Yi; Luo, Junting
Metal bellows used in the flexible connection of metallurgical converter oxygen lance compensates for pipeline displacement through its bending deformation, and adjacent waveforms in the concentrated deformation area are squeezed, resulting in premature fracture. The bending geometric model of U-shaped metal bellows is established in this paper, and the geometric relationship between waveform structure parameters and ultimate bending radius is derived. Moreover, a mathematical model of bending moment (M) with bending angular displacement (θ) about wave height H and wave crest fillet radius Rc is established. Then, combined with Fe-safe fatigue life analysis software, the fatigue life and failure location of metal bellows are obtained. The optimal waveform parameter design range of DN80 metal bellows with high repeated bending fatigue life under large bending is determined. Finally, the bending performance and fatigue life of bellows are tested on a bending fatigue testing machine. The distribution law of fatigue life and the propagation law of cracks at the wave trough of metal bellows under different bending angular displacement amplitudes are obtained. The crack propagation mechanism and fracture mechanism under different displacement amplitudes are revealed by a scanning electron microscope. In the engineering application of large bending, the pipeline failure caused by the ultimate bending deformation of metal bellows can be avoided according to the prediction results of fatigue life.